The Influence of Knowledge Management, Work-Life Balance, and Commitment on Public Sector Employee Performance - Satrya, Aryana; Pangaribuan, Leviadi; Parasuraman, Balakrishnan (Integrated Journal of Business and Economics (IJBE), 2025)
This research investigates the impact of knowledge management and work-life balance on employee performance with the role of affective commitment as a mediator in the Indonesian public sector. Data were collected via an online questionnaire from 703 respondents who were Government Financial Institution (GFI) employees at the staff level with a minimum of one year of work experience. The questionnaire utilized a 7-point Likert scale measurement and data analysis was conducted using Structural Equation Modeling (SEM) techniques with Lisrel 8.8 software. The findings of the study indicate that knowledge management practices, work-life balance, and affective commitment positively and significantly influence employee performance. Additionally, affective commitment was found to partially mediate the direct relationships examined in this research. This study contributes to the field of Human Resource Management (HRM) by expanding the literature on knowledge management practices and work-life balance in the public sector, areas that have received limited research attention. Furthermore, this research offers novelty by investigating predictors of performance among public sector employees from Generation Y and Generation Z.